2016
DOI: 10.3233/bmr-150630
|View full text |Cite
|
Sign up to set email alerts
|

Postneedling soreness after deep dry needling of a latent myofascial trigger point in the upper trapezius muscle: Characteristics, sex differences and associated factors

Abstract: Soreness and hyperalgesia are present in all subjects after dry needling of a latent MTrP in the upper trapezius muscle. Women exhibited higher intensity of postneedling soreness than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
14
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
9
14
5
Order By: Relevance
“…In the present study, 94.2% of patients presented postneedling soreness, whereas other studies observed proportions of 55% [40,41], 88% [42], or 91.4% [13]. These proportions of subjects with postneedling soreness seem to be lower compared with other studies in healthy subjects [19][20][21]. Asymptomatic subjects may have a greater capacity to describe postneedling soreness in detail because it does not overlap with any myofascial pain.…”
Section: Postneedling Sorenesscontrasting
confidence: 83%
See 2 more Smart Citations
“…In the present study, 94.2% of patients presented postneedling soreness, whereas other studies observed proportions of 55% [40,41], 88% [42], or 91.4% [13]. These proportions of subjects with postneedling soreness seem to be lower compared with other studies in healthy subjects [19][20][21]. Asymptomatic subjects may have a greater capacity to describe postneedling soreness in detail because it does not overlap with any myofascial pain.…”
Section: Postneedling Sorenesscontrasting
confidence: 83%
“…Patients who received DDN with multiple needle insertions to elicit LTRs presented with greater postneedling soreness prevalence and intensity than those in the control group, who received one unique needle insertion out of the MTrP. In line with previous preliminary research in healthy subjects [21], the number of needle insertions was associated with the intensity of postneedling soreness. However, no differences were observed regarding postneedling soreness prevalence and pain intensity in between groups in which LTRs were elicited.…”
Section: Postneedling Sorenesssupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, the results suggest a delay effect after the dry needling technique with twitch response. There is also a relationship between the patient's gender and pain relief as well as the frequency needed to receive LTR until the end of the treatment so that there is no more LTR [33]. The study results are consistent with our study, especially in the group of dry needling without LTR.…”
Section: Discussionsupporting
confidence: 90%
“…A 2 × 3 mixed model ANCOVA with time (before and 72 hours after TrP‐DN) as the within‐subjects factor, group (experimental, placebo, control) as the between‐subjects factor, and gender as the covariate was used to determine the effects of TrP‐DN on pain and disability. Gender was used as covariate because previous research suggests that women experience more postneedling soreness than men [38]. For each ANCOVA, the hypothesis of interest was the group × time interaction.…”
Section: Methodsmentioning
confidence: 99%